The role of relativistic kinematics in describing two-quark systems - Lengyel, V.; Rubish, V.; Fekete, Yu.; Chalupka, S.; Salak, M. (Condensed Matter Physics, 1998)
An attempt to incorporate relativistic kinematics in the description of light quark systems is made. It seems that the way of such an incorporation suggested by R.Gaida and his collaborators is very promising. Comparison of these results with the experimental data concerning a boson mass spectrum shows that this approach is among the best theoretical interpretations of the data.